Predictive value of developmental testing in the second year for cognitive development at five years of age - Alastair G Sutcliffe; Audrey Soo; Jacqueline Barnes (MDPI AG, 2010)
There is mixed evidence about the predictive validity of the Griffiths mental developmental scales. This study aimed to assess the predictive value of developmental assessments of children in their second year using the Griffiths mental development scales for neuro-developmental status at five years using the Wechsler preschool and primary scale of intelligence, revised (WPPSI-R). In a longitudinal study 253 children were assessed in their second year of life using the Griffiths scales and again at five years using the WPPSI-R. The scores were compared and the predictability of the WPPSI-R outcome on the basis of Griffiths scores was assessed. The WPPSI-R full scale IQ and the performance IQ at age five could be predicted moderately by the Griffiths general quotient (GQ) and by the personal/social scale. The Griffiths GQ was not a significant predictor of verbal IQ at age 5. The Griffiths performance scale predicted subsequent WPPSI-R performance IQ, and marginally the Full Scale IQ. For the early identification of children at risk for language delay, the Griffiths scales may not be suitable. However, a shortened form would be useful to predict overall cognitive development from the second year to school entry, focussing on the personal-social and performance scales.